Algas marinas bentónicas de Isla Mujeres, Quintana Roo, México - Mendoza-Gonzalez, A. Catalina; Mateo-Cid, Luz Elena (Instituto de Ecología, A.C., 1992)
Results are presented of a study on benthic marine algae from the Caribbean waters, of Isla Mujeres, Quintana Roo, México. The floristic list ineludes data on distribution of spedes,  reproductivo stage, tidal level, mode, fades and epiphytism. Ten spedes of Cyanophyceae, 122 spedes of Rhodophyceae, 33 spedes and 1 variety of Phaeophyceae, 6 spedes of Bacillariophyceae and 74 spedes, 1 variety and 10 forms of Chlorophyeeae were identified.Spedes diversity was compared for two different dimatic seasons, the rainy and the dry, during 1983, 1984, 1985 and 1987. Differences in the total number of species found in each dimatic seasons were significant. The number of spedes of Cyanophyceae, Bacillariophyceae and Phaeophyceae was constantly lower than the number of the Rhodophyceae and Chlorophyceae.The spedes of the families Caulerpaceae and Udoteaceae, together with Thalassia testudinum are the principal components of the benthic marine vegetation of Isla Mujeres. The algal flora of Isla Mujeres is tropical, ¡t blooms in spring-summer during the rainy season. Spedes diversity in relation to facies, light, temperature and tides is discussed.